Elevated HIV prevalence and risk behaviours among men who have sex with men (MSM) in Vietnam: a systematic review. Issue 5 (26th September 2012) - García, Macarena C; Meyer, Samantha B; Ward, Paul
Abstract : Objectives: To review and analyse original studies on HIV prevalence and risk behaviours among men who have sex with men (MSM) in Vietnam. Design: Systematic literature review. Comprehensive identification of material was conducted by systematic electronic searches of selected databases. Inclusion criteria included studies conducted from 2002 onwards, following a systematic review concluding in 2001 conducted by Colby, Nghia Huu and Doussantousse. Data analysis was undertaken through the application of both the Cochrane Collaboration and ePPI Centre approaches to the synthesis of qualitative and quantitative studies. Setting: Vietnam. Results: Sixteen studies, undertaken during 2005–2011, were identified that met the inclusion criteria. The analysis showed that HIV prevalence among MSM in Vietnam has increased significantly (eg, from 9.4% in 2006 to 20% in 2010 in Hanoi) and that protective behaviours, such as condom use and HIV testing and counselling, continue at inadequately low levels. Conclusions: Increasing HIV prevalence and the lack of effective protective behaviours such as consistent condom use during anal sex among MSM in Vietnam indicate a potential for a more severe HIV epidemic in the future unless targeted and segmented comprehensive HIV prevention strategies for MSM in Vietnam are designed and programmes implemented.